Symbolic physics and fantastic literature: a methodological interview for the interpretation of Las Fuerzas extrañas - Esparza, Gustavo (Revista de Letras, 2018)
The present work proposes that it is possible to interpret Las fuerzas extrañas of Leopoldo Lugones applying the symbolist methodology proposed by the German physicist Heinrich Hertz and philosophical considered by Ernst Cassirer. I will argue that applying this methodology, two results are possible: i) a new reading of Argentinean work´s and ii) the identification of life as the phenomenological and hermeneutic key of his work.